Persepsi Pemuda Terhadap Pekerjaan di Bidang Pertanian di Kecamatan Pamona Timur Kabupaten Poso - Pelima, Joice Noviana; Bunga , Nurfhin Ilma; Panemba, Monicafei Greta (Interdisciplinary Journal (IDe), 2024)
This study aims to determine youth perceptions toward jobs in the agricultural sector and the factors that influenced youth perceptions toward jobs in the agricultural sector. This research was conducted in East Pamona District, Poso Regency, from March to June 2023. The data sources used in this study were primary data and secondary data. The population is 3809 youths, while the sample is 100 youths.  The analytical instrument used was quantitative descriptive analysis.  The results showed that the youth in Pamona Timur District had a positive perception toward jobs in the agricultural sector, with a total score of 2626. Besides, the expectation of youth in East Pamona District is exceptionally favorable toward jobs in the agricultural sector. In addition, the factors that can influence the perception of youth in the Pamona Timur Subdistrict towards job in the agricultural sector are the family environment and land ownership status. Prestige is the reason why the young people in East Pamona District rarely work in the agricultural sector.